Breakpoint regions of ETO gene involved in (8; 21) leukemic translocations are enriched in acetylated histone H3. Issue 11 (13th September 2013) - Stuardo, Marcela; Nicovani, Sandra; Javed, Amjad; Gutierrez, Soraya
ABSTRACT One of the most frequent chromosomal translocation found in patients with acute myeloid leukemia (AML) is the t(8;21). This translocation involves the RUNX1 and ETO genes. The breakpoints regions for t(8;21) are located at intron 5 and intron 1 of the RUNX1 and ETO gene respectively. To date, no homologous sequences have been found in these regions to explain their recombination. The breakpoint regions of RUNX1 gene are characterized by the presence of DNasaI hypersensitive sites and topoisomerase II cleavage sites, but no information exists about complementary regions of ETO gene. Here, we report analysis of chromatin structure of ETO breakpoint regions. Chromatin immunoprecipitation (ChIP) were performed with antibodies specific to acetylated histone H3, H4, and total histone H1. Nucleosomal distribution at the ETO locus was evaluated by determining total levels of histone H3. Our data show that in myeloid cells, the breakpoint regions at the ETO gene are enriched in hyperacetylated histone H3 compared to a control region of similar size where no translocations have been described. Moreover, acetylated H4 associates with both the whole ETO breakpoint regions as well as the control intron. Interestingly, we observed no H1 association either at the breakpoint regions or the control region of the ETO gene. Our data indicate that a common chromatin structure enriched in acetylated histones is present in breakpoint regions involved in formation of (8;21) leukemic translocation. J. Cell. Biochem. 114: 2569–2576, 2013. © 2013 Wiley Periodicals, Inc.